MUC1, MUC5AC, and MUC6 polymorphisms, Helicobacter pylori infection, and gastric cancer: a systematic review and meta-analysis. Issue 4 (July 2018) - Giraldi, Luca; Michelazzo, Maria B.; Arzani, Dario; Persiani, Roberto; Pastorino, Roberta; Boccia, Stefania
Abstract : The risk of Helicobacter pylori (HP) infection, as well as gastric cancer (GC), in association with genetic polymorphisms of gene encoding for mucins, has been investigated with contradictory results. We carried out this systematic review and meta-analysis to summarize the relationship between MUC1, MUC5AC, and MUC6 polymorphisms and HP infection, as well as GC risk. We searched MEDLINE, ISI Web of Science, Scopus bibliographic databases and the HuGE Navigator database. Odds ratios (ORs) and 95% confidence interval (CI) were calculated to assess the association between the genetic polymorphisms, and HP/GC risk. A random-effect model was used to calculate the pooled ORs, overall and by ethnicity. Twenty-one studies were included, of which five on HP and 18 on GC, of which two were in common. The meta-analysis of 10 studies on the MUC1 rs4072037 polymorphism and GC risk reported an OR of 0.66 (95% CI: 0.57–0.78) for the dominant model (AG/GG vs. AA). When stratifying for ethnicity, an OR of 0.73 (95% CI: 0.62–0.86) was reported for the Asian population and an OR of 0.48 (95% CI: 0.38–0.61) was reported for the White population. Our study confirms the protective effect of MUC1 rs4072037 polymorphism on the risk of GC under the dominant model. Further studies reporting information on HP status in cases and controls would be required to evaluate whether the protective effect of MUC1 protein might be attributable to a protective effect towards the HP infection, or through different mechanisms.